Faith Inspired Leadership and Teacher Professionalism in Madrasah Principals in Indonesia - Adiyono Adiyono; Agus Zaenul Fitri; Refika Refika; Ali Said Al Matari; Silvia Arianti; Hendra Ani Iswiyanto; Ashimatul Alai (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study explores the role of the madrasah principal in enhancing teacher professionalism, highlighting leadership practices, the factors that support and inhibit it, and strategic solutions in the Indonesian Islamic education context. A qualitative case study approach was employed at MA Al Ihsan Tanah Grogot in the 2023/2024 academic year. Data were collected through in-depth interviews with principals and teachers, direct observations, and document analysis. Thematic analysis was conducted to identify leadership patterns and professional development strategies. The findings reveal three key insights: (1) the principal plays multi-dimensional roles as an educator, manager, supervisor, and motivator in strengthening teacher professionalism; (2) supporting factors include strong collegiality, religious motivation, and accreditation-driven improvement, while inhibiting factors include limited resources, teacher workload, and inconsistent discipline; (3) effective solutions are found in motivational leadership, structured professional development, and a faith-based approach to teacher guidance. This research contributes to the literature on educational leadership in Islamic schools by presenting a context-specific model of principal leadership that integrates pedagogical, managerial, and spiritual dimensions. The study highlights how faith-informed leadership fosters sustainable teacher professionalism, offering implications for similar institutions in developing countries.